Development of Defocus Atomic Force Microscope (DeF-AFM). Issue 1 (2nd January 2023) - Cheng, Chung-Hsiang; Wang, Wei-Min; Huang, Kuang-Yuh
ABSTRACT: In this study, a novel measuring instrument named defocus atomic force microscope ( DeF-AFM ) is presented. A Gaussian beam intensity measuring method is proposed for this optical pickup unit (OPU)-based AFM. Only partial components inside the OPU such as the laser diode, the objective, and the photodiode IC ( PDIC ) are required for this method. The displacement of the cantilever can be acquired by analyzing the exponential intensity change, which is along the optic axis of the laser, reflected to the PDIC. A support controller for the DeF-AFM is also designed and developed. The dynamic measuring ranges of this AFM in X, Y, and Z-axis are designed to be 12, 000 nm, 12, 000 nm, and 1400 nm, respectively. The horizontal and the vertical resolution are approximately 3.3 nm and 0.34 nm, respectively. The spatial resolution of the DeF-AFM is also verified by resolving the single atomic layer of the highly ordered pyrolytic graphite ( HOPG ).